#TITLE_ALTERNATIVE# - PUSPITANINGRUM (NIM: 10311003); Pembimbing : Dr. Hakim L. Malasan, EVARIA
Deriving the physical parameters of Planetary Nebulae (PN) by using the empirical method gives the uncertainty and lack of accurate. Photoionization model is used as an alternative to derive silmutaneously and sel consitently physical parameters of PN from a set of observed quantities, such as electron temperature, electron density and abundances in PN. The physical parameters of NGC 6543 and NGC 7662 is derived by using empirical and photoionization model method. Spectroscopic study of emission lines is used to determine the electron temperature, electron density and abundances of PN. The spectrogram of NGC 6543 and NGC 7662 is observed at Koyama Astronomical Observatory by using low resolution spectrograph (R = 500). The photoionization model is built by using photoionization code Cloudy C13.03. The modeled and spectroscopic electron temperature for NGC 7662 are 9500 K and 13700 K, while for NGC 6543 are 8850 and 8500 K. Both of them are using emission lines of [O III]. While the modeled electron density usually have big deviation with the observed temperature. It is might be because of the intensity measurement of emission lines [SII] are not too accurate. The abundances of helium, oxygen and neon between the modeled and observed in NGC 6543 have deviation value of -0.002, -0.009 and -0.01. While the abundances of helium, oxygen and sulfur in NGC 7662 have deviation value of 0.006,-0.005 and 0.001.